Interspeech 2016 2016
DOI: 10.21437/interspeech.2016-554
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach to Modeling Empathy in Addiction Counseling

Abstract: Motivational interviewing is a goal-oriented psychotherapy, employed in cases such as addiction, that aims to help clients explore and resolve their ambivalence about their problem. In motivational interviewing, it is desirable for the counselor to communicate empathy towards the client to promote better therapy outcomes. In this paper, we propose a deep neural network (DNN) system for predicting counselors' session level empathy ratings from transcripts of the interactions. First, we train a recurrent neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
(14 reference statements)
1
41
0
Order By: Relevance
“…Although most of the research efforts focus on the therapist's language and speech, it has been shown that examining patient's language can be beneficial for specific behavior cues [9]. More recently, text-only approaches to assess MI have been possible thanks to deep learning models [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the research efforts focus on the therapist's language and speech, it has been shown that examining patient's language can be beneficial for specific behavior cues [9]. More recently, text-only approaches to assess MI have been possible thanks to deep learning models [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This type of model architecture allows successful learning from long sequences, helping to capture diverse time scales and remote dependencies. Practical aspects on the use of LSTMs and other deep learning architectures can be found in [18].…”
Section: Supervised Learningmentioning
confidence: 99%
“…The Counselor Observer Ratings Expert for Motivational Interviewing (CORE-MI) is an automated coding and visualization system that provides report-card like feedback on psychotherapists’ adherence with MI [24]. CORE-MI combines speech and language processing with automated coding and interactive visualization to help counselors and trainers identify strengths and areas for improvement (Figure 1).…”
Section: Core-mi Overviewmentioning
confidence: 99%